Sosialisasi Membangun Keterampilan Public Speaking di SMA Katolik 2 Kabanjahe - Sembiring, Jenita Anjani Br; Simamora, Indah; Verbina , Sita; Sitepu, Sri Asih; Sembiring, Manzalina (EDUPEDIA Publisher, 2024)
Public speaking is a valuable talent that every person should have today. As a result, it is critical that we recognize the importance of introducing this skill to pupils at a young age. With the goal of preparing pupils to express their ideas and views loudly and confidently. With today's highly advanced technology breakthroughs, students' public speaking skills must undoubtedly grow in order to strengthen their character as they face their future. The urgency of this school's research stems from the fact that students' public speaking skills in the classroom are still considered subpar. As a result, both instructors and students participated.